Renalase attenuates hypertension, renal injury and cardiac remodelling in rats with subtotal nephrectomy. Issue 6 (29th February 2016) - Yin, Jianyong; Lu, Zeyuan; Wang, Feng; Jiang, Zhenzhen; Lu, Limin; Miao, Naijun; Wang, Niansong
Abstract: Chronic kidney disease is associated with higher risk of cardiovascular complication and this interaction can lead to accelerated dysfunction in both organs. Renalase, a kidney‐derived cytokine, not only protects against various renal diseases but also exerts cardio‐protective effects. Here, we investigated the role of renalase in the progression of cardiorenal syndrome (CRS) after subtotal nephrectomy. Sprague–Dawley rats were randomly subjected to sham operation or subtotal (5/6) nephrectomy (STNx). Two weeks after surgery, sham rats were intravenously injected with Hanks' balanced salt solution (sham), and STNx rats were randomly intravenously injected with adenovirus‐β‐gal (STNx+Ad‐β‐gal) or adenovirus‐renalase (STNx+Ad‐renalase) respectively. After 4 weeks of therapy, Ad‐renalase administration significantly restored plasma, kidney and heart renalase expression levels in STNx rats. We noticed that STNx rats receiving Ad‐renalase exhibited reduced proteinuria, glomerular hypertrophy and interstitial fibrosis after renal ablation compared with STNx rats receiving Ad‐β‐gal; these changes were associated with significant decreased expression of genes for fibrosis markers, proinflammatory cytokines and nicotinamide adenine dinucleotide phosphate (NADPH) oxidase components. At the same time, systemic delivery of renalase attenuated hypertension, cardiomyocytes hypertrophy and cardiac interstitial fibrosis; prevented cardiac remodelling through inhibition of pro‐fibrotic genes expression and phosphorylation of extracellular signal‐regulated kinase (ERK)‐1/2. In summary, these results indicate that renalase protects against renal injury and cardiac remodelling after subtotal nephrectomy via inhibiting inflammation, oxidative stress and phosphorylation of ERK‐1/2. Renalase shows potential as a therapeutic target for the prevention and treatment of CRS in patients with chronic kidney disease.